2020
DOI: 10.1093/gerona/glaa160
|View full text |Cite
|
Sign up to set email alerts
|

External Resistance Is Imperative for Training-Induced Efferent Neural Drive Enhancement in Older Adults

Abstract: ABSTRACT Strength training performed with heavy loads and maximal intended velocity is documented to enhance efferent neural drive to maximally contracting musculature in older adults. However, it remains unclear whether the neural plasticity following training result from motor skill learning or if external resistance is a prerequisite. To investigate this, we assessed electrically evoked potentials (H-reflex and V-waves normalized to maximal M-wave) and volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The improvements in maximal strength and RFD were accompanied by increased efferent neural drive ( V max / M sup -ratio). Interestingly, we have recently documented, albeit in an elderly population, that a potential learning effect of training is not manifested as increased V max / M sup -ratio (Unhjem et al 2021 ). This strengthens the assumption with which we can assume that the increases observed in V max / M sup -ratio are an effect of the strength training itself, although we cannot rule out that a learning effect contributed to the increases in 1RM and RFD.…”
Section: Discussionmentioning
confidence: 93%
“…The improvements in maximal strength and RFD were accompanied by increased efferent neural drive ( V max / M sup -ratio). Interestingly, we have recently documented, albeit in an elderly population, that a potential learning effect of training is not manifested as increased V max / M sup -ratio (Unhjem et al 2021 ). This strengthens the assumption with which we can assume that the increases observed in V max / M sup -ratio are an effect of the strength training itself, although we cannot rule out that a learning effect contributed to the increases in 1RM and RFD.…”
Section: Discussionmentioning
confidence: 93%
“…In the other condition the participants were instructed to perform the concentric action as fast as possible, emphasizing a maximal intentional velocity (MIV), as previously used in our laboratory (Wang et al 2017;Unhjem et al 2021). The purpose of applying MIV is to maximally stimulate the neural descending motor drive to contracting musculature and thus to maximally recruit muscle fibers (Tøien et al 2018b;Unhjem et al 2021;Behm and Sale 1993). Importantly, the actual movement velocity is relatively slow, especially at higher intensities, despite the maximal intended velocity.…”
Section: Movement Velocitymentioning
confidence: 99%
“…Previous research has shown that DPN patients are slower to develop ankle and knee joint force, which has been attributed to diminished muscle activation [ 46 , 117 , 118 , 119 , 120 ]. This decrement in strength and power seen in patients with DPN can be further exacerbated in older adults who contend with age-related sarcopenia [ 14 , 121 ]. Engagement in regular RT has been demonstrated to be a primary intervention for increasing strength and power through neural adaptations across ages [ 122 , 123 , 124 ].…”
Section: Exercise-based Interventionsmentioning
confidence: 99%
“…Engagement in regular RT has been demonstrated to be a primary intervention for increasing strength and power through neural adaptations across ages [ 122 , 123 , 124 ]. The use of heavy external loads, high velocity movements, and motor skill learning within RT aids in the increase of efferent neural drive through improved motor unit recruitment, motor neuron firing frequencies, motor unit synchronization, and the attenuation of antagonist co-activation [ 14 , 125 ]. With these neuromuscular adaptations in mind, various RT programs have been utilized to help reduce fall risk through enhanced balance and stability, increased core strength, work efficiency, and skeletal muscle fiber size [ 126 , 127 , 128 ].…”
Section: Exercise-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation